Resilience processes and positioning of agroecological farmers in an urban horticultural fair in northwest Patagonia - Ladio, Ana Haydee (2023)
Background: Horticultural fairs are spaces that promote regional agrobiodiversity, transmitting and recreating multiple knowledge and emotions between horticulturists and customers. The adaptive processes by which fairs are sustained over time in the face of socio-economic, climatic, and sanitary changes are still little known. Considering the principles of socio-environmental resilience, the aims of this research were: 1) to analyze the positionings of horticulturists that favor the process of resilience in the Free Fair of Family Farmers from Nahuel Huapi, San Carlos de Bariloche (Patagonia, Argentina) and 2) to reflect on the vulnerabilities and challenges faced by this fair for its sustainability over time. Methods: A qualitative study was carried out that included interviews, participant observation, and virtual ethnography. Results: One hundred and eighty-six ethnospecies, mostly of exotic origin (99%) are part of the agrobiodiversity of the fair. The main principles that foster the resilience of the fair are: high agrobiodiversity and functional redundancy that reflect and promote local food customs; learning and connectivity for innovation and information exchange; and cooperation and adaptive systemic thinking based on experiences, attachment to the land, and reciprocity. The affective dimension crosses each of these principles, strengthening the cultural fabric of horticulturists and customers. However, the economic and cultural viability of the fair is uncertain, mainly due to the drastic socio-environmental changes that the region is experiencing. Conclusions: To reduce the vulnerabilities of the fair, it will be necessary to strengthen the principles mentioned above and to increase the participation of the broader levels of governance (technical and governmental sectors).